2017
DOI: 10.1111/jam.13299
|View full text |Cite
|
Sign up to set email alerts
|

Persistence analysis of poliovirus on three different types of fomites

Abstract: In protected indoor environments poliovirus can remain infective for weeks. The models identified by this study can be used in risk assessments to identify appropriate strategies for managing this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“… 2019 ; Tamrakar et al. 2017 ; Incardona 1974 ). These studies suggest that decay for these viruses is not a simple exponential, with norovirus being modeled by a Weibull function (Ailavadi et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2019 ; Tamrakar et al. 2017 ; Incardona 1974 ). These studies suggest that decay for these viruses is not a simple exponential, with norovirus being modeled by a Weibull function (Ailavadi et al.…”
Section: Discussionmentioning
confidence: 99%
“… 2019 ), and poliovirus being modeled by either a damped exponential (Tamrakar et al. 2017 ) or biphasic decay (Incardona 1974 ). Some of these models suggest multiple pathways for viral inactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Mocé-Llivina et al observed higher virus survival of poliovirus 1 on cellulose ester membrane filters at 4 • C as compared to RT [31]. Despite a significant reduction in viral infectivity, Tamrakar et al observed Poliovirus 1 survival on steel, plastic and cotton after three weeks, when kept at RT and 40-60% RH [32]. Mbithi et al compared Poliovirus 1 with Hepatitis A virus and showed, that poliovirus was inactivated on stainless steel after 24 h and 6 h at 20 • C + 95 ± 5% RH and 20 • C + 25 ± 5% RH, respectively [33].…”
Section: Poliovirusmentioning
confidence: 97%
“…It can cause high-risk infection in public places (Thornley et al 2011;Meadow et al 2014;Zhang et al 2016;Xiao et al 2018) and in confined spaces (Rheinbaben et al 2000;Rowlands et al 2014). Micro-organisms transfer to and from a solid surface when the surface is touched (Kotwal and Cannon 2014;Malcolm et al 2017;Tamrakar et al 2017). Some researchers have studied the spread of disease via fomite surfaces by quantifying the transmission of bacteria and/or viruses between the hands and various surfaces (Boone and Gerba 2007;Julian et al 2010;Larocque et al 2016).…”
Section: Introductionmentioning
confidence: 99%